Analyses of transmit antenna selection to enhance security performance in cooperative radio communication networks under wiretap channel - Le, Tien Si; Pham, Ngoc Thoa; Thieu , Doan Quang Huy; Pham, Ngoc Son (Journal of Technical Education Science, 2019)
In this paper, we investigate the physical layer security technique of a cooperative communication network with a source node having multiple transmitting antennas, in which these antennas provide the most optimal antenna to increase security performance to a destination node via a relay node in the presence of an eavesdropper node. Here, we propose and analyze a transmission antenna selection (TAS) solution to enhance security performance in the eavesdropping channel, the cooperative communication model between the source node including multiple transmitting antennas and a destination node through a relay node and the influence of the eavesdropping node. The secrecy performance is exactly evaluated based on the secrecy outage probability (SOP) of the main channel compared to the eavesdropping channel in the Rayleigh fading channels. Monte-Carlo simulation method is applied to verify simulations and theoretical analysis results in the proposed model. The results show that when using such multiple transmit antennas significantly enhanced the system’s security performance.